Kebapaan Dan Pencapaian Akademik Kanak-Kanak Bandar Dan Luar Bandar - Baharudin, Rozumah; Maliki, Nazli @Nazlina (Penerbit Universiti Sains Malaysia, 1998)
The present study determined the quality offathering and its relationship with the academic achievement of children from urban and rural areas. The study was conducted in the district of Kuala Terengganu (urban) and Setiu (rural), Terengganu. The stratified randomized sampling technique was utilized in identifying the sample, which consists of 114 Malay father-child dyads ( 60 urban, 54 rural) from intact family